Differences in Metabolomic Profiles by Birthplace in Mexican-Origin Hispanic Men Who Participated in a Weight Loss Lifestyle Intervention. Issue 1 (February 2023) - Lopez-Pentecost, Melissa; Garcia, David O.; Sun, Xiaoxiao; Thomson, Cynthia A.; Chow, H.-H. Sherry; Martinez, Jessica A.
Birthplace, as a proxy for environmental exposures (e.g., diet), may influence metabolomic profiles and influence risk of cancer. This secondary analysis investigated metabolomic profile differences between foreign and U.S.-born Mexican-origin (MO) Hispanic men to shed light on potential mechanisms through which foreign- and U.S.-born individuals experience differences in cancer risk and risk factors. Plasma samples from MO Hispanic men ( N = 42) who participated in a previous lifestyle intervention were collected pre-and post-intervention. Metabolomic profiles were characterized from samples using ultra performance liquid chromatography–quadrupole time of flight mass spectrometry (UPLC-QTOF). Models were visualized using supervised orthogonal projections to latent structures–discriminant analysis (OPLS-DA). Progenesis QI was used for peak integration and metabolite identification. Plasma metabolomic profiles differed between foreign- and U.S.-born pre-intervention (R2 = .65) and post-intervention (R2 = .62). Metabolomic profiles differed pre- versus post-intervention (R2 = .35 and R2 = .65) for the foreign- and U.S.-born group, respectively. Both endogenous metabolites and dietary components characterized differences between foreign- and U.S.-born participants pre- and post-intervention. Plasma metabolomic profiles from MO Hispanic men differed by birthplace. These results advance our understanding of relevant exposures that may affect cancer risk among MO Hispanic men born abroad or in the United States.